FAITH, FREEDOM, AND THE FUTURE: RECLAIMING INCLUSIVE DEMOCRATIC VALUES IN SOUTH ASIA - Siddiqui, Hassan Rasheed; Leghari, Asad (The journal of contemporary issues in business and government, 2007)
This research sheds light on why interfaith religious harmony is not just essential, but yadros in the context of Pakistan, referring back to the historic speech of Quaid at Muhammad Ali Jinnah on August 11th, 1947. In that monumental speech, Jinnah laid the foundations for a Pakistan in which all citizens — irrespective of their religious beliefs — would enjoy equal rights, dignity and freedom through a democratic framework, devoid of discrimination and sectarian bias. But now the reality is worrisome drift from that ideal, with increased intolerance, weakening institutions and young people turning away from political life. Stemming from academic inquiry and field experience, this research brings together insights based on first-hand experience from participating in two highly influential international platforms: The Strategic Planning meeting of the Liberal Youth South Asia (LYSA) in Delhi; The International Academy for Leadership (IAF) in Gummersbach, Germany. The two workings offered invaluable insider insights into liberal youth collective in South Asia, organizational as well as ideological challenges in Pakistan and its own frying pan moments; most notably, the crisis created during the Lahore seminar where the Future Youth Group (FYG) and Friedrich Naumann Foundation (FNF). The paper provides a thorough critique of systemic faults such as dynastic politics, institutional mismanagement, and the increasing misinterpretation of liberalism as Westernization. It also points to the increasing sense of disillusionment among the youth of Pakistan, who feel left out of the decision-making process due to corruption and lack of civic education, as well as broken political promises. Inspite of these obstacles the research underlines the moral and civic obligation of youth, intellectuals and civil society actors to preserve the pluralistic foundations of Pakistan through positive mobilization. Consequently, this study recommends policy options relatively formulated to counter the problem of violent extremism: youth empowerment, reforming education, fostering interfaith communication, and developing constitutional protection. These reforms are framed not just as a necessity for democratic revival but a prerequisite to a peaceful, inclusive and progressive Pakistan as well.